2009
DOI: 10.1111/j.1399-3038.2009.00896.x
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms amongst asthmatic children’s caregivers

Abstract: We wanted to find out, whether the number of depressive symptoms is higher amongst asthmatic children's caregivers, compared to international data, to the Hungarian population average, and to parents of children with chronic renal disease. Are these depressive symptoms connected to the children's psychological status, asthma severity or current asthma symptoms? One-hundred and eight, 7- to 17-yr-old asthmatic children were enrolled, who have been treated at the Semmelweis University, First Department of Pediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…Especially, in mothers of children with asthma, there are evidences to suggest that caregivers of children with asthma exhibit greater anxious and depressive symptoms compared with caregivers of healthy children. A previous study with asthmatic children's caregivers reported that prevalence of depression and anxiety in caregivers was higher than in the average population (Szabó et al, 2010). In the result of meta-analysis, caregivers of children with asthma had greater anxious and depressive symptom than caregivers of health children (Easter et al, 2015).…”
Section: ⅴ Discussionmentioning
confidence: 75%
“…Especially, in mothers of children with asthma, there are evidences to suggest that caregivers of children with asthma exhibit greater anxious and depressive symptoms compared with caregivers of healthy children. A previous study with asthmatic children's caregivers reported that prevalence of depression and anxiety in caregivers was higher than in the average population (Szabó et al, 2010). In the result of meta-analysis, caregivers of children with asthma had greater anxious and depressive symptom than caregivers of health children (Easter et al, 2015).…”
Section: ⅴ Discussionmentioning
confidence: 75%
“…Reported depression and anxiety is high among caregivers of children with asthma (Silver, Warman, & Stein, 2005; Szabo, Mezei, Kovari, & Cserhati, 2010), and is associated with higher number of unscheduled health care visits (Spurrier NJ et al, 2003). While some of these factors are typical to residence in urban inner-city neighborhoods and do not differ between Hispanics/Latinos and African Americans (Rastogi D, Madhok N, & Kipperman S, 2013), others including language barrier (Mosnaim GS et al, 2007), influence the quality of care provided to Hispanic/Latino families.…”
Section: Childhood Asthmamentioning
confidence: 99%
“…We recently found that community healthcare professionals significantly overestimate the risk of fatal anaphylaxis for children with food allergy, which may contribute to feelings of anxiety . Allergic comorbidities such as asthma are often present in those with food allergy, and these can also be associated with anxiety in affected children and their caregivers . While oral and epicutaneous immunotherapy show promise as treatments to reduce immunologic sensitivity in people with food allergy, there is a need for treatments which effectively address the psychological and emotional burden of the disease.…”
Section: Introductionmentioning
confidence: 99%